Antifouling membrane based on sodium alginate coated polyamide thin film composite for desalination of brackish water. Issue 11 (30th September 2020) - Kancherla, Ravichand; Vadeghar, Ramesh Kumar; Ginuga, Prabhaker Reddy; Sridhar, Sundergopal
Abstract: Sodium alginate coated polyamide thin film composite (SA/PA‐TFC) membranes were synthesized for the desalination of brackish water through reverse osmosis. Membranes were characterized by Fourier transform infrared spectroscopy, x‐ray diffraction, scanning electron microscopy, AFM, thermogravimetry, and universal testing machine for structural analysis, crystallinity, morphological, compositional, thermal, and mechanical properties, respectively. The effect of feed pressure on water flux and % salt rejection was quantified. Simulation results generated using the commercial process simulator PRO/II were in good agreement with the experimental data. Case studies using simulator were performed for brackish water with different salinity to optimize operating pressure based on product unit cost (PUC) by varying the feed pressure and membrane area. The calculated PUCs were found to be 0.9 and 0.3 $/m 3 for corresponding feed total dissolved solids (TDS) concentrations of 5000 and 500 mg/L at an optimum pressure of 10 bar, to achieve a salt rejection of 98% using a membrane area of 335 m 2 . We believe these membranes are a prospective solution for brackish water desalination. Abstract :